Digestibility of feeds in rabbit (0ryctolagus cuniculus linnaeus, 1758) in Africa: A review - ATCHADE, Ghislaine; HOUNDONOUGBO, M. FRÉDÉRIC; ATTAKPA, S. EUGÈNE; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; MENSAH, GUY APOLLINAIRE (My University, 2019)
Feed digestibility indicates how much the body uses feed and its nutrients. This study aims to make a literature review on the digestibility of balanced feed given to farmed rabbits in Africa. Data used for this literature review were collected through many scientific papers published from 2008 to 2018 and uploaded to Google Scholar, Pubmed, Agora search engines and in national university libraries. Numerous scientific studies in this field indicate that more than thirty feedstuffs are commonly used to formulate balanced feed delivered to rabbits in Africa. Feed digestibility is generally assessed in vivo by the direct method in farmed rabbits. The data compiled shows that the digestibility of feed by rabbits varies enormously depending on the feedstuffs in balanced feed and also on their incorporation rate. The data recorded by the various authors’ show that balanced feeds with an Apparent Digestibility greater than 50%.
Keywords: Balanced feed; In vivo digestibility; Farmed rabbit; Africa